The Authoritative historian : tradition and innovation in Ancient historiography - Kingsley, K. Scarlett; Monti, Giustina; Rood, Tim (Cambridge University Press, 2022)
In this volume an international group of scholars revisits the themes of John Marincola's ground-breaking Authority and Tradition in Ancient Historiography. The nineteen chapters offer a series of case studies that explore how ancient historians'approaches to their projects were informed both by the pull of tradition and by the ambition to innovate. The key themes explored are the relation of historiography to myth and poetry; the narrative authority exemplified by Herodotus, the'father'of history; the use of'fictional'literary devices in historiography; narratorial self-presentation; and self-conscious attempts to shape the historiographical tradition in new and bold ways. The volume presents a holistic vision of the development of Greco-Roman historiography and the historian's dynamic position within this practice.